Degradative inactivation of cyclic AMP-dependent protein kinase by a membranal proteinase is restricted to the free catalytic subunit in its native conformation. - Alhanaty, E (1981)
A membranal proteinase from brush-border epithelial cells of the rat small intestine was shown to bring about a restricted and limited degradation of the free catalytic subunit (C) of cyclic AMP-dependent protein kinase (ATP:protein phosphotransferase, EC 2.7.1.37) with concomitant inactivation of the kinase. This membranal proteinase exhibits a remarkable specificity. (i) It degrades C in its native conformation, but not after it has been heat-denatured. (ii) The degradation of C (Mr 40,000) does not proceed further, once a distinct clipped product (Mr 34,000) is formed. (iii) The undissociated ("stored") form of the enzyme (R2C2) is not attacked by the membranal proteinase, preserving both its potential catalytic activity and its molecular integrity. Only upon addition of cyclic AMP to release free C does the proteinase attack it. (iv) The membranal proteinase does not degrade the regulatory subunit (R), released by cyclic AMP from R2C2, although R is quite susceptible to degradation by other proteolytic enzymes. None of these features of the membranal proteinase could be reproduced with trypsin, chymotrypsin, clostripain, or papain. The specific, restricted, and limited action of this membranal enzyme raises the possibility that it may have a distinct physiological assignment associated with the bioregulation of cyclic AMP-dependent protein kinase.